CURRENT APPLICATION OF AI IN THE CREATION AND DEVELOPMENT OF BIOLOGY LEARNING MEDIA - Maulida, Maulida; Hasanah, Mauizah (Jurnal Biologi Sains dan Kependidikan, 2023)
Learning media in the form of videos is one option that can be presented for the learning process. The aim of this research is to produce a learning media that uses and applies various AI that are familiar to students' ages and lives. This research uses a project based learning model, where a media is produced as a final assessment in a program. The subjects in this research were 8 prospective teacher students in their 7th semester. The existence of this project is one solution to increase the number of learning media that can be used when students start to participate directly in practical field experience activities. Learning media assessment includes concepts, context and virtual appearance. The types of AI used by students consist of Canva, Capcut, Kinemaster, inshot, alight amation, picsart, and Beat.Ly. In the process of making learning videos, students will combine the use of AI because learning videos must have audio explanations, not just visual ones. The application of media with color and language, and also equipped with contemporary background songs, makes students who see the media more interested so that the learning process and the process of transferring material concepts becomes easier.